The Effect of Implementing Problem Based Learning (PBL) Learning Model Assisted by Interactive Media on Improving Problem Solving Skills and Self Efficacy of Learners - Talitha Zakia; Hafnati Rahmatan; Safrida S; M. Ali S; Ismul Huda (Postgraduate, University of Mataram, 2025)
Their self-efficacy or self-confidence, is related to active involvement in solving problems. This belief encourages students to be actively involved in learning and overcoming academic challenges. The solution offered is the application of the Problem Based Learning (PBL) learning model assisted by interactive website-based media. This interactive model and media allow students to be actively involved in learning, to improve their problem-solving skills and strengthen their self-efficacy. The purpose of this study was to analyze the application of the Problem Based Learning (PBL) model assisted by interactive media on improving problem-solving skills and self-efficacy of students. This research method uses a quantitative R&D approach. The population in this study was 143 students, with a sample of 72 students in class XI of SMAN 4 Banda Aceh. Data collection in this study used several techniques, namely the test technique (Problem Solving Skills essay questions) and non-test techniques (Self-Efficacy questionnaire). Based on the research results, it is known that there is an influence of the application of the PBL model assisted by interactive media on improving students' problem-solving skills on the reproductive system material at SMAN 4 Banda Aceh and there is a positive relationship between self-efficacy and students' problem-solving skills through the application of the PBL model assisted by media on the reproductive system material at SMAN 4 Banda Aceh.